Stair walking effects on feelings of energy and fatigue: Is 4-min enough for benefits? - Carmichael, Kaitlyn E.; O’Connor, Patrick J.; Gay, Jennifer L. (Frontiers in Psychology, 2022)
Purpose: Even low intensity exercise bouts of at least 15 minutes can improve feelings of energy and reduce systolic blood pressure. However, little is known about the psychological outcomes of briefer exercise bouts, particularly for modes of exercise that are more intense than level walking and readily available to many working adults. This study assessed the effects of a 4-minute bout of stair walking on feelings of energy (FOE) and feelings of fatigue (FOF). Methods: Thirty-six young adult participants were randomized to either stair walking or seated control groups. All participants walked on level-ground from a laboratory to a nearby stairwell (~90 sec) and were seated for 4 minutes before beginning their experimental condition. Stair-walking participants walked up and down one flight of 16 stairs at their own pace for 4 minutes, while control participants remained seated during that time. Participants walked back to the laboratory for post-condition assessments. Measures of blood pressure, heart rate, rated perceived exertion (RPE), and the intensity of feelings of mental energy, mental fatigue, physical energy, and physical fatigue were assessed pre- and post-condition. Separate one-way ANOVAs were conducted on change scores for all variables. Results: The stair climbing group experienced significant increases in heart rate (F(1,34) = 13.167, p <.001) and RPE (F(1,34) = 93.844, p <.001) that were not observed in the seated control group. Four minutes of self-paced stair climbing resulted in small changes and non-significant differences within and between groups in blood pressure as well as FOE and FOF. Conclusion: Although a 4-minute self-paced exercise bout can convey short-term physiological health benefits, a 4-minute bout of self-paced indoor stair walking in a stairwell was insufficient to lower blood pressure or change subjective feelings of energy and fatigue in a sample that exhibited better than typical feelings of energy and fatigue at the pre-test.